Assessment of heavy metal pollution sources and environmental capacity of typical farmland soils in northwestern Zhejiang based on the geological background of black rock series - Mei-hua Wang (Frontiers in Environmental Science)
IntroductionMost studies have not fully considered the impact of heavy metal pollution sources on soil environmental capacity. However, a detailed analysis of pollution sources helps to more accurately assess regional environmental capacity and its dynamic changes, providing new research ideas and theoretical support for the management, early warning, and treatment of heavy metal pollution. Changshan County in the western Zhejiang province, as an important agricultural county, has increasingly prominent soil heavy metal pollution issues with the advancement of industrialization and urbanization. However, the current situation of regional environmental capacity remains unclear.MethodsThis study focuses on the black shale geological background of the county, collecting 1,788 farmland soil samples. The enrichment factor method was used to assess the enrichment levels of heavy metals in the soil, and principal component analysis and correlation analysis methods were employed to clarify the main sources of heavy metals in the farmland soil. Using Geographic Information System (GIS) technology and geostatistical methods, the environmental capacity characteristics of farmland soil heavy metals and their spatial distribution patterns were assessed.ResultsThe results show that the average concentrations of ω (Cd), ω (Hg), ω (As), ω (Pb), ω (Cr), ω (Ni), ω (Cu), and ω (Zn) in the surface soil of Changshan County’s farmland are 0.53, 0.12, 15.33, 34.03, 65.87, 29.06, 30.37, and 99.77 mg·kg−1, respectively. Except for Cd, which is moderately enriched, and Cr, which is not enriched, the other heavy metals show mild enrichment characteristics. Principal component analysis extracted four principal components with a cumulative contribution rate of 78.92%, and the spatial distribution differences were obvious. Cd Ni, Cu, Zn, As, Pb, Cr and Hg showed significant regional enrichment, and Cd was mainly affected by the dual influence of natural baseline and human disturbance. The static environmental capacity of heavy metals in the soil and the existing capacity rank in the same order: Cr > Zn > Pb > Ni > Cu > As > Hg > Cd. Their existing capacity average values are as follows: Cr 428.77, Zn 239.99, Pb 140.56, Ni 93.19, Cu 55.12, As 31.56, Hg 0.90, Cd −0.35 kg·hm−2. The comprehensive capacity index is 0.66. Moreover, the existing capacity of Cd in paddy fields is significantly lower than in drylands.DiscussionThe main sources of heavy metals in farmland soil are divided into four categories: mixed sources, natural sources, natural and industrial sources, and industrial sources. The comprehensive capacity index reflects that the overall environmental capacity level of farmland soil in the study area is low, and the problem of heavy metal pollution is relatively serious. In particular, areas such as Huibu Town, Baishi Town, Jinchuan Street, and Fangcun Town, which are jointly affected by geology and human activities, face higher environmental risks. This study strengthens the coupling research between environmental capacity and pollution source analysis, providing theoretical support for the prevention and remediation of heavy metal pollution in the farmland soil of Changshan County, as well as a new research pathway for assessing the dynamic changes in regional environmental capacity.